2021
DOI: 10.3126/janr.v4i1.33231
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effectiveness of storage structures for maintaining the quality of maize seed stored at different moisture levels

Abstract: One of the main causes of food insecurity is the timely unavailability of quality seeds for smallholder farmers in developing countries. Improved storage technologies are effective in reducing storage losses. Thus, the objective of this research is to assess the traditional and emerging seed storage structures/materials for the maintenance of seed qualities. The effect of different storage conditions (moisture content of seed at the time of storage, i.e. 12±0.15% and 13.5±0.18%; storage containers such as meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
3
2
0
Order By: Relevance
“…In contrast, the moisture content in the hermetic bags remained at safe storage levels throughout the entire 6‐month storage period. These findings align with previous studies that have demonstrated the effectiveness of hermetic bags in maintaining stable seed moisture content 14,15,18,36 . Similar results have been reported for other crops, such as green grams, where moisture content increased in PP and jute bags but remained consistent in hermetic bags over a 6‐month storage period 37 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In contrast, the moisture content in the hermetic bags remained at safe storage levels throughout the entire 6‐month storage period. These findings align with previous studies that have demonstrated the effectiveness of hermetic bags in maintaining stable seed moisture content 14,15,18,36 . Similar results have been reported for other crops, such as green grams, where moisture content increased in PP and jute bags but remained consistent in hermetic bags over a 6‐month storage period 37 .…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, significantly higher levels of chickpea grain damage (ranging from 14.3% to 35.5%), weight loss (8.3% to 22%), and dockage (1%) were observed in non‐hermetic storage units compared to hermetic bags, which exhibited mean values of 2.2% to 3.2%, 0.43% to 1.27%, and 0.3% for grain damage, weight loss, and dockage, respectively. Similar findings have been reported in various other stored agricultural products such as common bean, 38 field pea, 16 green gram, 37 Dolichos Bean, 43 chickpea, 14 cowpea, 41 maize, 15,22,36,39,47 and wheat, 29 highlighting the higher levels of grain damage and weight loss in grains stored in traditional storage facilities compared to improved hermetic storage technologies.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations